The Rise and Fall of National Bargaining in the Canadian Meat-Packing Industry - Forrest, Anne (Relations industrielles / Industrial Relations, 1989)
The author addresses the questions of why industry-wide bargaining was developed in the Canadian meat-packing industry and why it suddenly collapsed.